Performance and stability of femtosecond laser-irradiated Fe2O3 materials as photocatalysts for methylene blue dye discoloration - Souza, Josiane Carneiro; Martins, Tiago Almeida; de Oliveira, Regiane Cristina [UNESP]; Sambrano, Julio Ricardo [UNESP]; Mendonça, Cleber Renato; de Boni, Leonardo; Leite, Edson Roberto; Longo, Elson (Ecletica Quimica, 2022)
The disposal of substances pollutant, such as methylene blue dye (MB), into wastewater, arouses the interest of technologies to remove these pollutants. The discoloration of MB by photocatalysis and using femtosecond laser-irradiated Fe2O3 materials as photocatalysts proved to be a promising way to treat this pollutant. Here, Fe2O3 obtained by the conventional hydrothermal process and heat-treatment, subsequently femtosecond laser-irradiated treatment. Materials obtained with a mixture of irradiated α-Fe2O3 and ε-Fe2O3 phases revealed lower crystallinity than irradiated α-Fe2O3 samples. The irradiation treatment and the increase in crystallinity were crucial to improve the performance of α-Fe2O3 irradiated sample in the discoloration of MB, which reached 90% in 75 min of dye solution exposure under UV irradiation. The irradiation treatment proved to allow greater exposure of the particle surfaces, which coalesced and presented a greater distribution of medium size, indicating a more heterogeneous morphology in the irradiated samples. As a result, there was an increase in active sites due to the density of defects generated, which facilitated the dye degradation process.
Keywords: defect density; dye; pollutant; polymorphism